2013
DOI: 10.1021/am303268k
|View full text |Cite
|
Sign up to set email alerts
|

Cu Ion Ink for a Flexible Substrate and Highly Conductive Patterning by Intensive Pulsed Light Sintering

Abstract: Direct printing techniques that utilize nanoparticles to mitigate environmental pollution and reduce the processing time of the routing and formation of electrodes have received much attention lately. In particular, copper (Cu) nanoink using Cu nanoparticles offers high conductivity and can be prepared at low cost. However, it is difficult to produce homogeneous nanoparticles and ensure good dispersion within the ink. Moreover, Cu particles require a sintering process over an extended time at a high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 26 publications
5
110
0
Order By: Relevance
“…Similarly, printed electronics are limited by variation of the conductivity or porosity across a printed feature. [17][18][19] Biological assays based on inkjet technology also need a uniform concentration of material across the deposit to be most effective.…”
Section: -8mentioning
confidence: 99%
“…Similarly, printed electronics are limited by variation of the conductivity or porosity across a printed feature. [17][18][19] Biological assays based on inkjet technology also need a uniform concentration of material across the deposit to be most effective.…”
Section: -8mentioning
confidence: 99%
“…For this reason, copper nanoparticles have received considerable attention due to their lower cost; however, copper nanoparticles can be easily oxidized and cannot be sintered by thermal sintering under ambient conditions. To solve these problems, various sintering methods such as laser irradiation [2], microwave [13] and precursor processes [14][15][16] were studied by several researchers. These approaches have limitations in mass production because of their low throughput, high complexity, and considerable environmental obstacles (e.g., high temperature or vacuum conditions).…”
Section: Introductionmentioning
confidence: 99%
“…However, Cu nanoparticle inks generally require high sintering temperatures above 300°C to obtain high conductivities [13,14]. To address this problem, photonic sintering using intense pulsed light with millisecond exposure times and a wide range of wavelengths has been reported as the most useful sintering method for the Cu nanoparticles [15][16][17][18]. A Cu nanoparticle layer can be converted to a highly conductive layer due to instantaneous heat generation within the layer accompanied by absorption of the intense pulsed light.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have reported improvements in layer conductivity or the reduction of sintering temperature for Cu nanoparticles, however they have focused on the application to interconnect technologies on flexible polymer film at low temperatures [15][16][17][18]. There have been few reports on the application of the printed Cu electrodes to TFT [13,14].…”
Section: Introductionmentioning
confidence: 99%